Beneficial fluid-dynamic features of pulsatile swirling flow in 45° end-to-side anastomosis. Issue 3 (March 2015) - Ha, Hojin; Choi, Woorak; Lee, Sang Joon
Highlights: Fluid-dynamic features in a 45° end-to-side anastomosis were investigated. Pulsatile swirling flow equalizes the wall shear stress distribution. Swirling flow reduces oscillatory shear index and the flow separation. Swirling flow disturbs secondary flow collision. Swirling flow should be considered for designing better vascular grafts. Abstract: Although a large number of vascular grafts are surgically implanted annually, approximately 10–15% of these grafts fail in the first year after operation and about 50% are only effective for five to ten years. Surgical implantation of a vascular graft modifies the inherent hemodynamic environment in blood vessels; hence, fluid dynamic characteristics of pathological blood flow are highly related to the performance of the vascular graft. In this study, pathological fluid-dynamic characteristics in a 45° end-to-side anastomosis were experimentally investigated using a particle image velocimetry technique. In particular, the effect of the pulsatile swirling inlet flow in the vascular graft on the improvement of pathological hemodynamic features was systematically investigated. Introducing the pulsatile swirling flow equalizes the asymmetric distribution of wall shear stress and reduces oscillatory shear index and the size of flow separation because the flow disturbs the formation of Dean-type vortices and suppresses secondary flow collision. The fluid dynamic features of the pulsatile swirling flow are expected to be beneficial in designing vascular grafts that can suppress pathological hemodynamic characteristics in the recipient host vessel.